PENGEMBANGAN GAME EDUKASI MATEMATIKA DASAR UNTUK ANAK SD BERBASIS UNITY 2D - Zulfikar Zulfikar; Muhammad Gibran Ardiansyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Mathematics is often considered difficult by elementary school students due to boring and overly theoretical teaching methods. To address this issue, the author developed an educational game titled “Ayo Berhitung!” (Let’s Count!), built using Unity 2D for Android. The game consists of 30 levels of math problems including addition, subtraction, multiplication, and division, structured in increasing difficulty. Features include randomized questions, score and star system, progress saving, child-friendly visuals, sound effects, and background music. The game was tested at MI Nurul Qur’an Ploso and received positive feedback from students, teachers, and parents. Test results show that the game can improve students’ interest and motivation in learning mathematics.